NFT Market Segmentation Classification of Buyer Behavior Based on Blockchain Type and Marketplace Platform Using Power BI Interactive Data Visualization - Ananda Marcella Suratman; Alyani Intan Shaffira; Farrel Pasya Harramain; Akhmad Bakhrun (Electronic Journal of Education, Social Economics and Technology, 2026)
The Non-Fungible Token (NFT) market has experienced rapid growth and high volatility, creating challenges for stakeholders aiming to understand transaction patterns and market behavior. This study addresses these challenges by employing an interactive Power BI dashboard to analyze and visualize NFT transaction data from 2021 to 2022. Grounded in descriptive and correlation analysis, the research is structured into three primary visual components: market summary, transactional insights, and correlation analysis. Using data visualization techniques and statistical correlation theory, the dashboard enables the identification of key performance indicators such as user activity, platform efficiency, and pricing dynamics. The findings reveal significant growth in NFT adoption, with 7,820 unique buyers, 7,872 sellers, and 4,327 creators contributing to the ecosystem. A strong positive correlation (r = 0.77) between current and sale prices indicates predictive potential in price behavior. Among blockchain platforms, Solana recorded the highest total sales US$13.0 million and royalty distributions 13,000, while LooksRare and Foundation stood out as the most profitable marketplaces for creators. The Collectibles category led in transaction volume, with collections like AbstractVerse attracting notable interest. While monthly transaction volumes varied, the overall market value remained relatively stable, peaking in December 2022. This study contributes to a deeper understanding of NFT market mechanics by combining data-driven analysis with interactive visual tools, offering valuable insights for creators, investors, and analysts navigating the digital asset landscape.